Combustor development and performance analysis for recuperated microturbine application - Liu, Yize; Nikolaidis, Theoklis; Gamil, Abdelaziz; Madani, Seyed Hossein; Sarkandi, Mohammad (American Institute of Aeronautics and Astronautics (AIAA), 2021)
In recent years, increased attention is paid to the microturbine MGT as a promising technology for combined heat and power (CHP) applications. An MGT has advantages of high reliability, high efficiency, lower manufacturing and maintenance costs, reduced vibration and noise levels, and clean emissions. Recuperation can further increase efficiency by recycling the heat from the turbine exhaust and preheating the air for combustion via a heat exchanger. Such a system will be realized by designing a combustion chamber that can meet various design and operability requirements. This paper presents an overview of the combustor development and provides CFD analysis on combustor performance and emissions. A single tubular combustor is designed, and the direct injection mode is applied to mitigate the autoignition and flashback risks resulting from the high preheating temperature. Heat transfer and cooling analysis indicate that ceramic liner is capable of tolerating high temperature using effusion cooling. Studies of flow characteristics, temperature field, pressure loss, and pattern factor are provided in detail. The effects of design parameters and methods (i.e., fuel-air mixture strength, cooling hole angles, dilution hole design approaches) are also discussed. Finally, the use of biomass is investigated and shows that it has the potential to achieve a high combustion efficiency and low emissions for the recuperated microturbine application.
View Video Presentation: https://doi.org/10.2514/6.2021-3637.vid